Overcoming indifference: what attitudes towards news tell us about building trust - Toff, B; Badrinathan, S; Mont'Alverne, C; Ross Arguedas, A; Fletcher, R; Nielsen, R (Reuters Institute for the Study of Journalism, 2021)
This report details findings from an original survey of news audiences in Brazil, India, the United Kingdom, and the United States. It examines attitudes towards media in each country, ideas about how journalists conduct themselves, and views about which sources of information can be trusted online and offline. The report focuses especially on people with minimal trust and finds some patterns across countries: the least trusting are not necessarily the most vocal critics who are often selectively trusting towards particular providers. Instead, the untrusting tend to be the least knowledgeable about journalism, most disengaged from how it is practised, and least interested in the editorial choices publishers make daily when producing the news. The primary challenge news media and journalists face from this part of the public is not hostility, but indifference. Earning their trust calls for a different approach than that required for other segments of the public.